Metodologia para o desenvolvimento de brinquedos - Beinlich, Simone (2017)
Although the survey of requirements is considered by the literature as the most important non-PDP phase to obtain the commercial success of the product, said survey is an activity little practiced by the toy industry. Scientific researches seek to study a requirements management within the PDP in a general and superficial way without differentiating the different types of consumers. Understanding what consumers expect from a particular product is a task that has several complications, because analysts and consumers tend to have different languages beyond the emotional factors that are involved. There is no development of toys, and may be more complex, considering that they are consumers as needs and desires and special needs, different from other types of consumers. Please, this work had as objective the development of a methodology to help in the identification of the wishes of the children's public in its image to know the attractive product to the consumer. The methodology was elaborated considering models and tools already used to develop products and activities already practiced by the toy industry. A simulation of the development of a toy has demonstrated that, using a methodology proposed in the work, it is possible to obtain the desires of the children, such as parents needs, to consider as pedagogues orientations and other stakeholders without product, to talk this information in product specifications, So the essence of customers' desires is not lost as the project continues to evolve.